Risk Sharing, Indivisible Labor and Aggregate Fluctuations - Jang-Ok Cho; Richard Rogerson (Queen's University, Department of Economics, 1990)
This paper studies fluctuations in a real business cycle model when there is a risk neutral agent present to offer insurance to workers. This economy is compared with one in which there is no risk neutral agent but labor is indivisible. In static models it is difficult to distinguish the risk sharing and indivisible labor economies, but in dynamic models with capital accumulation the indivisible labor model appears to perform better.
Keywords: 330